Embedding Education for Sustainable Development through the Well-being of Future Generations (Wales) Act 2015 - Hayles, Carolyn S. (European Journal of Sustainable Development, 2018)
The Well-being of Future Generations (Wales) Act 2015 is one of a very small number in the World that legislates for Sustainable Development (SD). The Act ensures Wales will make a positive contribution to the achievement of the UN’s global Sustainable Development Goals (SDGs), through its seven SDG or Well-being Goals (WbGs). This paper outlines the development, delivery, and feedback from participants on a University-wide stand-alone certificate set up by the University of Wales, Trinity Saint David’s sustainability institute, INSPIRE. The primary aim of the certificate is to encourage staff and student engagement with SD issues pertaining to the Act, including opportunities to debate topics on-line. The on-line certificate, which is non-credit bearing, takes participants on a journey through the seven WbGs, giving them an insight into the ambitions of the Goals, supported by research and case studies, which cut across economic, social, cultural and environmental themes. Following the first year of its implementation, the author describes feedback from staff and students taking part in the certificate, including perceived strengths and weaknesses. Going forward, feedback taken on board has improved the certificate for its relaunch during the 2018-19 academic year. Keywords: Sustainable Development, Teaching and Learning, Well-being, Wales, Universities